THE DEVELOMENT OF COMIC AS LEARNING MEDIA TO IMPROVE STUDENT’S MOTIVATION IN MOMENTUM AND IMPULSES FOR HIGH SCHOOL - Sondang, Ruth; Derlina, Derlina (UNIVERSITAS NEGERI MEDAN, 2022)
This study aims to: 1) develop interesting instructional media such comics can affect student’s motivation, 2) determine students’ motivation after using comic as learning media, and 3) determine the feasibility of comic and student’s responses on momentum and impulses topic. The study was placed at SMAN 2 Medan and the participants were 20 science students of grade 10th. The type of research with Pretest-Postest group design model. The ADDIE model used for prepared instructional design of Physics Comic. The data of expert’s validations, students’s response and motivations were collected by using questionnaire of experts’ validation, student’ responses and students’ motivation.The result of this study is the product of momentum and impulses comic.The result of material validation is ????̅=4.25 in the good category and instructional media validation is ????̅=4.50 in very good category. The assessment of students in the form of response questionnaire is ????̅=4.38 in very good category. It can be concluded that the momentum and impulses comic is feasible to use in learning and get positive responses from the students. Based on the results obtained, it can be concluded that the momentum and impulses comic is strongly feasible abd very good so that it can be used in the learning process.